Equine hepatocytes: isolation, cryopreservation, and applications to in vitro drug metabolism studies - Shibany, Khaled A.; Tötemeyer, Sabine; Pratt, Stefanie L.; Paine, Stuart W. (Wiley, 2016)
Despite reports of the successful isolation of primary equine hepatocytes, thereare no published data regarding the successful cryopreservation of these isolatedcells. In this study, a detailed description of the procedures for isolation, cryop-reservation, and recovery of equine hepatocytes are presented. Furthermore, theintrinsic clearance (Clint) and production of metabolites for three drugs werecompared between freshly isolated and recovered cryopreserved hepatocytes. Pri-mary equine hepatocytes were isolated using a two-step collagenase perfusionmethod, with an average cell yield of 2.47  2.62 9 106cells/g of perfused livertissue and viability of 84.1  2.62%. These cells were cryopreserved with Wil-liam’s medium E containing 10% fetal bovine serum with 10% DMSO. The via-bility of recovered cells, after a 30% Percoll gradient, was 77  11% andestimated recovery rate was approximately 27%. These puriﬁed cells were usedto determine the in vitro Clintof three drugs used in equine medicine; omepra-zole, ﬂunixin, and phenylbutazone, via the substrate depletion method. Cryopre-served suspensions gave a comparable estimation of Clintcompared to fresh cellsfor these three drugs as well as producing the same metabolites. This work pavesthe way for establishing a bank of cryopreserved equine hepatocytes that can beused for estimating pharmacokinetic parameters such as the hepatic metabolicin vivo clearance of a drug as well as producing horse-speciﬁc drug metabolites.